Grão e pão: o saber camponês de Jesus de Nazaré - Pertile, Cassiano Alberto (2022)
According to the testimony of the four Gospels in the New Testament, Jesus of Nazareth involved extensive peasant knowledge in the proclamation of his Good News of the Kingdom of God. In the research carried out in this Master's Dissertation, attention is directed to cereals and bread food. Specifically, the first chapter of the investigation seeks to bring together the moments in which Jesus intends to work with the earth, in order to make it produce the grains of barley and wheat. Plowing, sowing, germinating the grain underground, growing the plant, forming the grain in the ear, harvesting and threshing become matters. In the second chapter, we look for the moments in which Jesus of Nazareth, in his speeches, welcomes the process of transforming grain into bread. It starts with looking at the separation of grains from other materials via winnowing and sieving, in order to store them in the barn. After that, the grinding of the grains takes place, that is, the production of flour. Finally, with the fermentation and baking of the dough, we arrive at the much-desired food of bread. In short: the objective of this Dissertation is to bring together those elements that Jesus of Nazareth, according to the New Testament Gospels, highlights in relation to grain and bread. With this, it becomes visible how much Jesus is attentive to the socio-environmental dimensions of human life, and how his religious reflection is ecotheological